2014
DOI: 10.1158/0008-5472.can-14-0181
|View full text |Cite
|
Sign up to set email alerts
|

Snail Recruits Ring1B to Mediate Transcriptional Repression and Cell Migration in Pancreatic Cancer Cells

Abstract: Transcriptional repressor Snail is a master regulator of epithelial–mesenchymal transition (EMT), yet the epigenetic mechanism governing Snail to induce EMT is not well understood. Here, we report that in pancreatic ductal adenocarcinoma (PDAC), elevated levels of the ubiquitin E3 ligase Ring1B and Snail, along with elevated monoubiquitination of H2A at K119 (H2AK119Ub1), are highly correlated with poor survival. Mechanistic investigations identified Ring1B as a Snail-interacting protein and showed that the ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 27 publications
2
50
1
Order By: Relevance
“…We found that E3 ubiquitin ligase RNF2, a PcG protein, is also associated with SFMBT2/YY1 at the promoters. Although the function of RNF2 has not been determined in prostate cancer progression, knockdown of RNF2 by siRNA abolished SNAIL-mediated E-cadherin repression and induced cell migration in pancreatic cancer cells [56]. …”
Section: Discussionmentioning
confidence: 99%
“…We found that E3 ubiquitin ligase RNF2, a PcG protein, is also associated with SFMBT2/YY1 at the promoters. Although the function of RNF2 has not been determined in prostate cancer progression, knockdown of RNF2 by siRNA abolished SNAIL-mediated E-cadherin repression and induced cell migration in pancreatic cancer cells [56]. …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this notion, we demonstrate that the inhibition of either ERK or eHsp90 ablates the EZH2 repressive mark in histone lysates, further reinforcing an eHsp90-ERK regulatory node for EZH2 function. As EZH2 cooperates with a panoply of cofactors to elicit the repressive function (37,(45)(46)(47), further work will be required to delineate the accessory factors mediating EZH2 recruitment to E-cadherin, as well as how eHsp90-ERK signaling may impact upon these associations.…”
Section: Discussionmentioning
confidence: 99%
“…A significant amount of growth factors such as TGF-β, HGF, EGF, IGF and FGS are known to trigger EMT process through a cascade of down-regulation E-cadherin expression [9]. E-box binding transcription factor such as Snail, Twist and ZEB1, were reported to epigenetically regulate E-cadherin expression through modification of the chromatin structure [10]. However, how these transcription factors are regulated has seldom been discussed.…”
Section: Introductionmentioning
confidence: 99%